2014
DOI: 10.1007/s10620-014-3435-5
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity Links Vinculin to the Pathophysiology of Chronic Functional Bowel Changes Following Campylobacter jejuni Infection in a Rat Model

Abstract: Host anti-CdtB antibodies cross-react with vinculin in ICC and myenteric ganglia, required for normal gut motility. Circulating antibody levels and loss of vinculin expression correlate with number of C. jejuni exposures and SIBO, suggesting that effects on vinculin are important in the effects of C. jejuni infection on the host gut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 47 publications
3
70
0
5
Order By: Relevance
“…Consistent with the fact that an absence or reduced frequency of these contractions is known to induce SIBO [5,21], the reduction in ICCs correlated with the development of SIBO in these rats [20]. Antibodies to CdtB were found to bind elements of the neuromuscular apparatus of the gut, including ICCs and myenteric ganglia [22]. This pattern of staining was also seen in small intestinal sections from rats that were never exposed to C. jejuni, and from human subjects who did not have IBS [22], suggesting that antibodies to the CdtB toxin were cross-reacting with a neuronal protein in the host gut.…”
Section: Autoimmunity and Ibssupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with the fact that an absence or reduced frequency of these contractions is known to induce SIBO [5,21], the reduction in ICCs correlated with the development of SIBO in these rats [20]. Antibodies to CdtB were found to bind elements of the neuromuscular apparatus of the gut, including ICCs and myenteric ganglia [22]. This pattern of staining was also seen in small intestinal sections from rats that were never exposed to C. jejuni, and from human subjects who did not have IBS [22], suggesting that antibodies to the CdtB toxin were cross-reacting with a neuronal protein in the host gut.…”
Section: Autoimmunity and Ibssupporting
confidence: 62%
“…Antibodies to CdtB were found to bind elements of the neuromuscular apparatus of the gut, including ICCs and myenteric ganglia [22]. This pattern of staining was also seen in small intestinal sections from rats that were never exposed to C. jejuni, and from human subjects who did not have IBS [22], suggesting that antibodies to the CdtB toxin were cross-reacting with a neuronal protein in the host gut. Through a series of studies, this was identified as the cytoskeletal protein vinculin [22].…”
Section: Autoimmunity and Ibsmentioning
confidence: 89%
“…24 The levels of circulating host antibodies to CdtB correlated with levels of small intestine bacterial overgrowth, and these anti-CdtB antibodies cross-reacted with the enteric neural protein, vinculin, likely through molecular mimicry. 24 A recent large scale study including a total of 2681 subjects (2375 IBS-D subjects, 43 healthy subjects, 121 celiac, and 142 IBD subjects) demonstrated that anti-CdtB antibodies had a sensitivity of 43.7% and a specificity 91.6% at a cut-off value of ≥ 2.80 to discriminate IBS-D from IBD. 25 Anti-vinculin antibodies had a sensitivity of 32.6% and a specificity of 83.8% at a cut-off value of ≥ 1.68 to distinguish IBS-D from IBD.…”
Section: Specific Biomarkers For Diarrhea-predominant Irritable Bowelmentioning
confidence: 97%
“…La razón es que los anti-CdtB se han encontrado relacionados con la disminución de las células intersticiales de Cajal en modelos animales de SII-post C. jejuni lo cual se asocia con sobrepoblación bacteriana del intestino delgado (SIBO) y disbiosis secundaria a dismotilidad 78 . Estudios posteriores mostraron la presencia de una reacción cruzada de la anti-CdtB contra la vinculina del hospedero, una proteína necesaria para el acoplamiento de las cateninas con los filamentos de actina que se requiere para la contractilidad del músculo liso intestinal 79 . De esta manera, la presencia de anticuerpos antivinculina inhibe la motilidad y predispone a la SIBO 79 .…”
Section: Anticuerpos Anti-fracción B De La Toxina De Distensión Citolunclassified
“…Estudios posteriores mostraron la presencia de una reacción cruzada de la anti-CdtB contra la vinculina del hospedero, una proteína necesaria para el acoplamiento de las cateninas con los filamentos de actina que se requiere para la contractilidad del músculo liso intestinal 79 . De esta manera, la presencia de anticuerpos antivinculina inhibe la motilidad y predispone a la SIBO 79 . Siguiendo esta teoría, tras una gastroenteritis, un subgrupo de pacientes desarrolla SII-PI inicialmente por la presencia de anti-CdtB, seguido por anti-vinculina.…”
Section: Anticuerpos Anti-fracción B De La Toxina De Distensión Citolunclassified